Evaluation of diagnostic accuracy of alpha-fodrin antibody in Iranian patients with Sjogren's disease - Alireza Rostamian; Azar Baradaran; Peyman Mottaghi; Mansour Salesi; Mansour Karimifar; Vahid Mansouri (Advanced Biomedical Research, 2022)
Background: Sjogren's syndrome, as a chronic autoimmune disease, involves in lymphocytic infiltration in the exocrine glands. As the result of exocrine glands disruption, the clinical hallmark of this disease including dryness of mouth and eyes along with fatigue and joint pain occur. However, heterogeneity of clinical presentations among newly diagnosed adult patients with Sjogren's syndrome leads to difficulty in its diagnosis. One of the diagnostic criteria for Sjogren's syndrome is the presence of autoantibodies in patient serum. One of the novel biomarkers suggested for diagnosis of Sjogren is alpha-fodrin antibody. In this study, we aimed to evaluate the diagnostic power of anti-α-fodrin antibody among the Iranian population for the first time. Materials and Methods: We recruited 82 individuals in this study. Alpha-fodrin were measured in case and control with Elisa kit as 16.71 (9.84) and 18.44 (11.54). Results: There was no any significant difference between two groups regarding alpha-fodrin level (P = 0.35). Then we applied the receiver operating characteristic (ROC) curve analysis to determine the predictive value of alpha-fodrin for diagnosing Sjogren's disease. The area under curve of the ROC curve was calculated as 0.5453. Also, there were significant association between age and alpha-fodrin antibody. Conclusions: Alpha-fodrin test did not have acceptable predictive power for predicting Sjogren's disease; however, it could be associated with disease progression.